2023
DOI: 10.20525/ijrbs.v12i1.2283
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effectiveness of e-customer service platforms on customer satisfaction at ABSA, Botswana

Abstract: The study's primary objective was to analyze the effectiveness of e-customer service platforms on customer satisfaction in commercial banks in Botswana, using ABSA bank as a case study. The secondary objectives were to assess the effectiveness of reliability, responsiveness, assurance, empathy and tangibles of e-customer service platforms on customer satisfaction at ABSA bank. A positivist research philosophy was adopted. A cross-sectional survey design was used to collect data and probability sampling was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Undoubtedly, satisfying customers is not sufficient; hence, the need to explore the antecedents and outcomes of customer delight in an environment characterised by oligopolistic behaviours. As a developing African market, Botswana's service delivery has become a critical differentiator for the country's banking industry (Chiguvi, 2016). Theoretically, the results of this study may provide clarity on the relevance of RM in elucidating the relationship between the antecedents of surprise as well as delight and loyalty intention.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Undoubtedly, satisfying customers is not sufficient; hence, the need to explore the antecedents and outcomes of customer delight in an environment characterised by oligopolistic behaviours. As a developing African market, Botswana's service delivery has become a critical differentiator for the country's banking industry (Chiguvi, 2016). Theoretically, the results of this study may provide clarity on the relevance of RM in elucidating the relationship between the antecedents of surprise as well as delight and loyalty intention.…”
Section: Introductionmentioning
confidence: 76%
“…Regardless of the adoption of new technologies and innovations in service delivery, challenges remain that are related to customer attraction, satisfaction, delight and loyalty (Agolla et al, 2018). In addition, research confirmed that customers in Botswana's banking industry are not entirely satisfied with the services provided by banks (Chiguvi, 2016).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, Kadeswaran, Brindha and Jayaseelan (2020:p.4880) support that "social media also provides women with an online space to express their options as well as share content related to their emotions and/or happenings in and around them without any barriers related to content, imagination or geographical boundaries". On top of that, Chiguvi (2023) insists that social media sites provide spots for seeking knowledge for addressing various needs among users, an opportunity which can also be utilised by women in empowering themselves financially. The interactive feature of WhatsApp speedup inclusive and the practice of digital economy in the group which is a key element for women economic empowerment.…”
Section: Findings and Discussionmentioning
confidence: 99%